Handling Optimization of Reports and Complaints by Unit I Criminal Investigation Division to Accelerate the Follow-Up of Cases in Semarang Police Department - Pakurimba, Silvester Rante Mas (Advances in Police Science Research Journal, 2024)
Accelerating the follow-up of handling criminal case reports or complaints is one of the efforts to create a law enforcement system that can provide legal certainty. Based on the research conducted, there are findings in Unit I Criminal Investigation Division of Semarang Police Department that investigators do not immediately raise reports or complaints into Police Reports because they make their handling directly monitored by the Electronic Investigation Management technology system of the Police Criminal Investigation Division. The writing of this final project is the result of field research with a qualitative approach. Primary sources used come from interviews and observations. This is supported by secondary sources derived from scientific articles and previous studies on handling public complaints. The informants in this research are (1) Police elements; (2) other law enforcement elements; (3) NGOs; and (4) the community. The data collected is described in descriptions, figures, and tables to explain the study's findings. The study results show the ability of police organizational resources and the stages of the mechanism in handling reports or complaints of theft, stealing, and carjacker cases from the public carried out by Unit I Criminal Investigation Division of Semarang Police Department need to be revised. This can be seen from the significant difference in data between the number of reports or complaints received and the issuance of police reports. Hence, this final project aims to optimize the Handling of Reports or Complaints by Unit I Criminal Investigation Division to Accelerate the Follow-up of cases at Semarang Police Station.